Constructing Students Disciplinary Character through Hidden Curriculum in the Pesantren Tradition: An Educational Technology Perspective - Amelia Sapitri; Noviriani Noviriani; Muallimin Muallimin; Nur Hikmah; Hijriah Afika; Muhammad Sabli (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2022)
This study analyses the construction of students disciplinary character through the hidden curriculum mechanism in the Islamic boarding school tradition at Pondok Pesantren Al Fatah, while examining the role of educational technology as a mediating factor in the pesantren moral ecosystem. The research employed a qualitative approach with a single case study design. Informants were selected through purposive sampling, consisting of seven senior students and three teachers. Data were collected through participatory observation, in-depth interviews, and document analysis, then analysed following the interactive model of Miles, Huberman, and Saldana, including data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, method triangulation, and member checking. The findings reveal that disciplinary character is constructed through collective prayer habituation, structured rules with social supervision, teacher role modelling, and peer reinforcement culture. Discipline evolves from external compliance toward internalised awareness embedded in students identities. Selective adoption of educational technology reinforces the hidden curriculum through activity monitoring, documentation of moral practices, and enrichment of learning content, although it also introduces risks of distraction from open digital media exposure. The study confirms that the pesantren tradition functions as a moral ecosystem that systematically reproduces values through structured daily practices. The findings imply the need for educational technology integration designs that are sensitive to the pesantren hidden pedagogy, so that digital transformation reinforces rather than replaces existing character formation mechanisms.